Oxynoemacheilus zarzianus, a new loach from the Lesser Zab River drainage in Iraqi Kurdistan (Teleostei: Nemacheilidae) - Freyhof, Jörg; Geiger, Matthias (Zootaxa, 2017)
Oxynoemacheilus zarzianus, new species, is described from the Lesser Zab River drainage, a tributary of the lower Tigris. It is distinguished from other Oxynoemacheilus species in the Tigris drainage by having a slightly emarginate caudal fin, no suborbital groove in males, a complete lateral line, the posterior process of the bony air-bladder capsule directed posteriorly, the flank and posterior part of back covered by scales, short barbels and a deep caudal peduncle. It is the fourth Oxynoemacheilus species known from the Lesser Zab drainage, where such loaches seem to be highly isolated in headwaters. Oxynoemacheilus species diversity in the Euphrates and Tigris drainage is exceptional high. Today 22 species are known from the entire Euphrates and Tigris drainage and 15 from the Tigris drainage alone.